The sustainable management of the landscape - Jean-David Gerber; Raimund Rodewald; Peter Knoepfel (Revue de Géographie Alpine)
The landscape is increasingly perceived as a resource. For this reason, it is necessary to find legal, political and economic instruments that will succeed in managing this "resource landscape" in the long term. The Swiss government recently introduced the instrument of regional nature parks into the legislation governing nature and landscape preservation; the proposed parks are organized on the basis of the French model. The examination of the new parks from the perspective of much older management structures, i.e. the civic municipalities (bourgeoisies) and corporations, makes it possible to demonstrate the strengths and weaknesses of each of these instruments in their contribution to the resolution of use rivalries between actors who use or influence the resource landscape. This comparison also enables the formulation of practical recommendations regarding the management of this resource.